2017
DOI: 10.1200/jco.2016.70.3413
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Model and Tool for Assessing Risk of Persistent Pain After Breast Cancer Surgery

Abstract: Purpose Persistent pain after breast cancer surgery is a well-recognized problem, with moderate to severe pain affecting 15% to 20% of women at 1 year from surgery. Several risk factors for persistent pain have been recognized, but tools to identify high-risk patients and preventive interventions are missing. The aim was to develop a clinically applicable risk prediction tool. Methods The prediction models were developed and tested using three prospective data sets from Finland (n = 860), Denmark (n = 453), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 29 publications
7
103
0
2
Order By: Relevance
“…Although efforts have been made to identify patients at risk for persistent pain after breast surgery, the relationship between persistent pain and chronic opioid use has not been delineated . Previous studies have shown that patient psychological characteristics (psychological “robustness” and tolerance of pain) can profoundly impact perception of pain and other symptoms as a consequence of breast surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Although efforts have been made to identify patients at risk for persistent pain after breast surgery, the relationship between persistent pain and chronic opioid use has not been delineated . Previous studies have shown that patient psychological characteristics (psychological “robustness” and tolerance of pain) can profoundly impact perception of pain and other symptoms as a consequence of breast surgery .…”
Section: Discussionmentioning
confidence: 99%
“…62 Using these predictive factors, validated risk-stratification tools have been developed to provide an individualised indication of risk, potentially enabling targeting of resources or early intervention. 63…”
Section: Risk Factors For Cpspmentioning
confidence: 99%
“…persistent pain after breast cancer treatment (18)(19)(20). Therefore, the contribution of treatment-related variables, such as type of surgery and adjuvant treatment modalities (radiotherapy, chemotherapy, trastuzumab), and different types of hormone therapy to higher levels of central sensitization, has to be evaluated.…”
mentioning
confidence: 99%